The effect of eggshell powder (ESP) filler on the properties of purple sweet potato (PSP) starch bioplastics / Faiezah Hashim ... [et al.] - Hashim, Faiezah (Research Management Institute (RMI), 2024)
Petroleum-based plastics are derived from non-renewable sources and are supremely utilized in packaging industries due to their superior flexibility, mechanical and barrier properties. However, due to petroleum-based plastics do not degrading easily, researchers are turning into bioplastics. This study was conducted to examine the effect of eggshell powder (ESP) loadings on the physical and mechanical properties of purple sweet potato (PSP) starch bioplastics. PSP starch was extracted and mixed with glycerol as plasticizer and 0 – 40 % by weight of ESP to fabricate PSP/ESP bioplastic using solution casting method. The incorporation of ESP in PSP starch matrix (in terms of functional groups and bonding existed) was analyzed by using Fourier Transform Infrared spectroscopy (FTIR-ATR). The physical property of PSP/ESP bioplastics is characterized through water absorption test. Whereas the mechanical properties (tensile strength, Young’s Modulus and elongation at break) of bioplastics was analyzed by tensile test. From FTIR analysis, it can be summarized that the PSP/ESP bioplastic was successfully synthesized. The tensile strength and modulus of this bioplastics increase from with the addition of ESP up to 20 wt.%. This is because further addition of ESP above 20 wt.% reduces tensile strength and modulus of elasticity of this bioplastic. In terms of elongation at break, a slight decrease in elongation at break as the ESP loadings increases. Similarly, the water absorption capacity of this bioplastic significantly decreases as the percentage of ESP increases. The incorporation of ESP into this bioplastic able to reduce rate of water absorption from 26.32 % to 12.5 % in 72 h. Therefore, these bioplastics exhibit good physical and mechanical properties that can be used as alternatives for synthetic plastic to cope with waste generation and disposal problems, especially in the food industry.